PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI DANA ZAKAT DI GAMPONG BALOY KECAMATAN BLANG MANGAT KOTA LHOKSEUMAWE - Hakim Hasibuan, Ahmad Fauzul; Abbas, Ichsan; Fuadi, Fuadi; Hasan, Nazli; Nur, Muhklis Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2021)
The purpose of this community service is to increase community understanding of the concept of zakat distribution in Baloi Village, Blang Mangat District, Lhokseumawe City. Specific targets in this community service are increasing community income in Baloi Village, Blang Mangat District, Lhokseumawe City, and how to improve community welfare through the zakat fund zakat of the Malikussaleh University Amil Zakat Agency (BAZMAL). The material that will be delivered at this community service is: community knowledge of the concept of zakat, then distribution of zakat funds to the community in Baloi Village, Blang Mangat District, Lhokseumawe City. Which is related to improving the welfare of coastal fishermen in Baloi Village, Blang Mangat Subdistrict, Lhokseumawe City. BAZMAL) Malikussaleh University.